Some reflections on the prospects for the harmonization of international business laws in Africa : OHADA and beyond - Fombad, Charles Manga (Africa Today, 2013)
The evidence of developments in the harmonization of international business laws shows that Africa is lagging seriously behind. There are still some skeptical voices about the need for and the value of harmonization of international business laws, but such voices are now in a minority. The aim of this paper is to assess the prospects for harmonizing international business laws in Africa. The main contention is that the debate today in Africa is not whether or not there should be harmonization of international business laws, but how this should be done. The paper reviews the imperatives for harmonization and the options that exist and then focuses on the present approach to harmonizing business laws in Africa under the auspices of the Organization for the Harmonization of Business Laws in Africa, better known under its French acronym, OHADA. Based on the critical review of the weaknesses and strengths of the OHADA regulatory framework, the paper suggests ways in which the agenda to develop a harmonized and modern set of business laws in Africa can be achieved.

Some perspectives on durability and change under modern African constitutions - Fombad, Charles Manga (International Journal of Constitutional Law, 2013)
A major cause of political and constitutional instability in post-independence Africa was the ease with which political leaders subverted constitutionalism by arbitrarily changing constitutions to suit their political agendas. During the constitutional reforms of the 1990s many provisions were introduced in most African constitutions aimed at limiting the ability of governments to abusively change constitutions. Because of the critical importance of controlling the process of constitutional change to entrenching constitutionalism, this paper attempts to critically examine and analyze some of the different control devices that have been introduced. The objective is to see to what extent they may help not only to promote constitutionalism but also enhance constitutional durability and stability. The first part considers why it is important for constitutional designers to include special procedures to regulate and control the constitutional amendment process. The second part examines the different amendment patterns in a number of selected African countries. The third part considers the practical implications of the various control devices in terms of their actual and potential impact on the nurturing and growth of constitutionalism on the continent. The paper concludes that although there has been some progress, more changes still need to be introduced to check the problem of arbitrary constitutional change in Africa.